Emerging forest ecosystem service entrepreneurship in Finland and Peru - Hiedanpää, Juha; Salo, Matti (Commonwealth Forestry Association, 2017)
Ecosystem services have been under intensive research and policy interest during the past two decades, resulting in advanced theoretical understanding and a variety of innovative policies. However, as economic approaches to ecosystem services are gaining foothold, co-creation of ecosystem services through entrepreneurial activity has been almost totally neglected in scientific discourse. By focusing on recent developments in the forests of Finland and Peru, we show how forest ecosystem service entrepreneurs are introducing new ecosystem service-related livelihood initiatives, business models and economic mechanisms. Scientists and policy-makers are showing a growing interest in how these bottom-up initiatives actually happen and what it takes to create new socioecological opportunities. The new discourse is critical toward the habit of mind to see a wide ontological and epistemological gap between the use and protection of ecosystems as well as between the abstracted practices of many ecosystem service approaches and particular forest use practices.
Keywords: development discourse; ecostructure; forest livelihoods; ecosystem services; entrepreneurship; livelihoods; forests